ВОЗМОЖНОСТИ НООТРОПНОЙ ТЕРАПИИ ПОГРАНИЧНЫХ ПСИХИЧЕСКИХ РАССТРОЙСТВ У ПАЦИЕНТОВ, ПЕРЕНЕСШИХ ОСТРЫЙ КОРОНАРНЫЙ СИНДРОМ, В УСЛОВИЯХ КАРДИОЛОГИЧЕСКОГО СТАЦИОНАРА - В. Э. Медведев; К. В. Зверев; А. В. Епифанов; О. А. Ларцева; Н. Л. Зуйкова; В. И. Фролова (SINAPS LLC, 2013)
One of the important problems at the intersection of cardiology and psychiatry is the choice of treatment of mental and neurotic disorders, level in patients with cardiovascular disease (CVD) in a cardiology hospital. Particular significance and the search for preventive agents for the prevention of psychopathology that influence the dynamics of somatic illness. In an open prospective study with a comparison group in a cardiology hospital demonstrated the efficacy and safety of the acute and prophylactic treatment of neuroprotective drugs Pantogam asset (an average dose of 1.8 and 1.2 g/day, respectively), borderline mental disorders in patients undergoing acute coronary syndrome (ACS).